Palladium-Catalyzed Reactions of Allylic Boronic Esters with Nucleophiles: Novel Umpolung Reactivity - Unsworth, Phillip J.; Löffler, Lorenz E.; Noble, Adam; Aggarwal, Varinder K. (Synlett, 2015)
Oxidative palladium-catalyzed reaction conditions have been developed to allow for regioselective and stereoselective coupling of allylic boronic esters with a range of carbon-, oxygen-, and nitrogen-based nucleophiles. Studies into the mechanism of the reaction have shown that the key transmetalation step occurs with retention of stereochemistry, since overall inversion is observed.
Keywords: palladium; boronic ester; umpolung; allylation; oxidative coupling